A COMPARATIVE LINGUISTIC ANALYSIS OF THE CONCEPTS OF “SMILE” AND “TABASSUM” IN ENGLISH AND UZBEK (European Journal of Interdisciplinary Research and Development, 2024)
The concepts “smile/tabassum” has culturally specific meanings in many languages as well as universal emotional expressions. This study explores the linguistic aspects that underpin the expression and perception of smiling in English and Uzbek, as well as how the words “smile/tabassum” is linguistically and culturally actualized in these languages. This research paper clarifies how “smile/tabassum” represent different cultural values through a comparative cultural analysis. Although smiling is a positive social tool in both languages, the results show that its applications and social interpretations differ greatly, underscoring the impact of cultural norms on language use.